2020
DOI: 10.1002/jsfa.10446
|View full text |Cite
|
Sign up to set email alerts
|

Processing of coconut sap into sugar syrup using rotary evaporation, microwave, and open‐heat evaporation techniques

Abstract: Background: Coconut sugar has a caramel color with a taste like brown sugar. It is commonly used as natural sweetener. However, coconut sugar has been produced from coconut sap using a traditional method that involves heating the sap at high temperature (>100 °C) in an open pan for a long period (3-5 h). This conventional method results in an over-cooked sugar, which leads to quality deterioration in terms of both its physical and chemical properties. The current study aimed to investigate the processing of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…In addition, different processing methods can also affect the sugar profiles. Previous studies have shown that several methods conducted on coconut sap, such as rotary evaporation and microwave, resulted in different sugar profiles and physicochemical properties (Asghar et al ., 2020c,b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different processing methods can also affect the sugar profiles. Previous studies have shown that several methods conducted on coconut sap, such as rotary evaporation and microwave, resulted in different sugar profiles and physicochemical properties (Asghar et al ., 2020c,b).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they should be increasingly used [ 20 ]. For studying organic constituents, the non-volatile ones are analyzed mainly by high-performance and ultrahigh liquid chromatography (HPLC/UHPLC) coupled to different detectors (e.g., refractive index (RI), mass spectrometry (MS), UV-Vis), while volatile ones are determined mostly by GC–MS (gas chromatography coupled to mass spectroscopy) (e.g., [ 21 , 22 , 23 ]). Indeed, coupling a chromatography system (e.g., UHPLC/HPLC or GC) to a mass spectrometer is one of the most powerful ways to identify and quantify compounds because this analytical strategy provides two different types of data per run analysis: (i) retention time and (ii) mass spectral pattern (molecular ion and fragmentation), for each separated compound.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Аналіз літературних джерел та формулювання проблеми Серед існуючих методів концентрування харчових розчинів найбільш поширеним є випарювання, що забезпечує отримання якісного харчового концентрату при відносно невисоких витратах на обладнання [7, ]. Досить високу популярність набирають дослідження даного процесу з використанням мікрохвильових ( ) технологій на прикладі різних фруктових і овочевих соків: ананасу [9,10], яблука [11], кокосу [12], гранату, винограду, моркви [13]. одібний науковий ажіотаж обумовлюється високими якісними показниками готового продукту, оскільки при електромагнітному підводі енергії відсутня класична теплопередача, що в свою чергу унеможливлює утворення прикордонного шару і, як наслідок, продукт не набуває присмаку варіння.…”
Section: вступunclassified